2014
DOI: 10.1111/wrr.12204
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative treatment of thyroidectomy scars using botulinum toxin: A split‐scar, double‐blind randomized controlled trial

Abstract: Operational scars, especially those located on the exposed parts of the body, can be distressing. Despite high demand for an early intervention to minimize surgical scars, there is yet no universal consensus on optimal treatment. A split-scar, double-blind randomized controlled trial was held to assess the safety and efficacy of early postoperative botulinum toxin type A (BTA) injection in surgical scars. A single session of treatment was performed where BTA was allocated to one half of the scar and 0.9% salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 31 publications
2
82
0
1
Order By: Relevance
“…Each of the patients’ scar was divided in half, each half received either BoNT‐A or saline injection. On the 6 months follow‐up, there was statistically difference in scar appearance in all 15 patients that completed the study between the side that received BoNT‐A injection and the side that received normal saline injection …”
Section: Bont‐a In the Prevention And Treatment Of Pathological Scarsmentioning
confidence: 98%
“…Each of the patients’ scar was divided in half, each half received either BoNT‐A or saline injection. On the 6 months follow‐up, there was statistically difference in scar appearance in all 15 patients that completed the study between the side that received BoNT‐A injection and the side that received normal saline injection …”
Section: Bont‐a In the Prevention And Treatment Of Pathological Scarsmentioning
confidence: 98%
“…A total of 7 studies reported patient satisfaction (Figure ), of which, the study of Wang Yang et al used the questionnaire survey covering scar hypertrophy, recovery progress, discomfort, ecchymosis, and psychological impact; the study of Xu Zhigang et al used a 10‐point value to evaluate the scar of patients, which were not included in this comparison due to the lack of specific data; The remaining five studies used “very satisfied,” “satisfied,” “slightly satisfied” and “dissatisfied”, or “satisfied,” “average” and “dissatisfied” for rating. We defined the percentage of the sum of options other than the “dissatisfied” in the total number as patient satisfaction, and the heterogeneity test suggested limited heterogeneity between studies ( χ 2 = 3.30, P = .51, I 2 = 0%<50%), so the fixed effect model was adopted, RR = 1.19[95%CI:(1.11,1.29), P < .00001]; The results showed that there was significant difference in patient satisfaction between the two groups, among which the patient satisfaction in the BTXA group was significantly higher than that in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (14) included 15 patients >18 years of age with a recent (<10 days) thyroidectomy neck scar with a mean length of 8 cm in a randomized, controlled split-scar study. Excluded were patients who were allergic to botulinum toxin, pregnant or lactating, suffering from myasthenia, injected with the toxin in the previous six months and those who refused to participate.…”
Section: Characteristics Of Included Studies and Potential Biasmentioning
confidence: 99%
“…The randomization was based on a generator setting the left or right side with number 0 or 1. Both the patients and the dermatologist performing the injections were blinded, while the other examiners were absent from the injection room (14).…”
Section: Characteristics Of Included Studies and Potential Biasmentioning
confidence: 99%
See 1 more Smart Citation